The Effectiveness Of Video Education Media Via Whatsapp Group On The Knowledge Of Mothers Of Toddler Ages 0-6 Months About Stunting - Gusfianti, Elsa; Wati, Dwi Retno; Suryani, Lilis; A’yun, Sofa Qurrata (Karsa Husada Health Institute Garut, 2024)
Stunting is a condition where a toddler has less length or height compared to his age. One of the causal factors is knowledge. This research aims to determine the effectiveness of educational video media via WhatsApp groups on the knowledge of mothers of toddlers aged 0 - 6 months about stunting. This type of research uses a quasi-experiment with a research design using one group pretest-posttest. Sample selection used a random sampling technique with a sample size of 40 people. Data collection was carried out using a questionnaire. Statistical tests non-parametric tests used the Wilcoxon test. The research results obtained before the respondents received stunting education, the sample had sufficient knowledge as many as nine people (22.5%) and 31 people (77.5%) had insufficient knowledge, whereas after the respondents received the stunting education video via WhatsApp group the sample had good knowledge as many as 40 people (100%). The results of the Wilcoxon test obtained a p value of 0.000, meaning that there was a significant increase in respondents' knowledge after the stunting educational video was conducted using WhatsApp. It is hoped that parents of toddlers will prefer to seek information by discussing with health workers via WhatsApp.